Justicia longipetiolata, a new species of Acanthaceae from Yunnan, China - Tong, Yi; Lin, Zheli; Deng, Yunfei (Phytotaxa, 2019)
A new species of Justicia (Acanthaceae), J. longipetiolata, is described and illustrated from Yunnan, China. The new species belongs to Justicia sect. Harnieria, and it is similar to J. championii and J. quadrifaria, but differs by the caudate leaf apex, obviously long petiole, short calyx and the length ratio of calyx to mature capsule. It is assessed to be “Least Concern” (LC) according to IUCN Red List Category and Criteria. Morphological characters of pollen grains and seeds are also reported.